Note on the Manufacture of Ferromanganese in the Blast Furnace - F. Valton (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1878)
(Read at the Wilkes-Barre Meeting, May, 1877.) IN the number of the Engineering and Mining Journal for April 7th, 1877, Mr. W. P. Ward, of Cartersville, Georgia, explains in a very interesting manner, the results he obtained in the manufacture of ferromanganese in the blast furnace. These results may be summed tip as follows : Production in the blast furnace of an alloy containing 67.2 per cent. manganese and 3 per cent. of carbon at most, with a utilization of the manganese amounting to 58 per cent. With the exception of the indicated proportion of carbon, which should be almost doubled to express the true state of facts, we would have had no observations to make on Mr. Ward's paper had he taken into account the results obtained in the same line in other centres of production. Before 1870, spiegel with 8 or 10 per cent. manganese only was known among blast-furnace products. In a journey to Sweden, in 1871, I ascertained that the Schysshyttan works manufactured regularly a spiegel with 18 per cent. manganese. Later, at the Vienna Exhibition, in 1873, the Sava and Jauerburg works, in Carniola, presented to the jury a ferromanganese, obtained in the blast fur-